Tissue effect on RNA:DNA ratios of marine fish larvae - Olivar, M. P. (2009)
In some routine studies of larval condition based on RNA:DNA ratios, heads and/or guts are removed for further age and feeding analysis. Also, during capture larvae are often found with their eyes missing. In this work we analysed tissues effects (muscle, head, eye, gut and the whole larvae) on RNA:DNA ratios from different species (Sardina pilchardus, Engraulis encrasicolus, Atherina presbyter and Paralichthys orbignyanus) in different developmental stages and from different locations. For all species and development phases, it was shown that RNA :DNA ratios in the head were significantly lower than in muscle or gut. The comparison of RNA :DNA ratios of head with or without eyes did not show significant differences. In a comparison of results from muscle from two tail sections, RNA :DNA ratios were higher for the anterior section in Sardina pilchardus and Engraulis encrasicolus larvae. Caution is needed when RNA :DNA ratios are compared with other studies employing different dissection protocols. For the species studied we propose conversion factors to be applied to RNA:DNA ratio data when different body sections are analysed. We discuss the most appropriate tissues for assessing nutritional condition in fish larvae, based on trends in concentrations of nucleic acids and ratios during starvation experiments.